Rubber-to-metal bonding: The effect of oil immersion, heat ageing and water absorption on peel strength - Jamal S N; Ahmad M A; Samsuri A (Journal of Rubber Research, 2014)
Rubber-to-metal bonded products find wide applications in the automotive industry where they are used as rubber springs. These products are exposed to heat, oil and water either deliberately or unintentionally during service. Studies were conduted to evaluate the peel strength of the rubber-to-metal bonded samples after they were subjected to oil immersion, heat ageing and water absorption. The vulcanisation systems and polarity of the rubber influenced the peel strength and durability of rubber-to-metal bonded samples. The conventional sulphur system gave higher peel strength and durability than the efficient vulcanisation (EV) system for both unaged and aged (70 degree C/14 days) samples. However, it is polarity of the rubber that is influenced most. The peel strength increased in an increasing order with polarity of the rubber, viz; NR<ENR25<ENR50<NBR because of the enhancement in interaction with the polar metal. The effect of polarity of the rubber on bond strength was marked after the samples were immersed in engine oil for seven days at ambient temperature. The peel strength increased in an increasing order with the polarity of the rubber. Apart from better interaction with the polar metal, polar rubber was more resistant to swelling than the non-polar rubber when immersed in hydrocarbon oil. Within the 30 days period of immersion in distilled water and salt water, there was no sign of deterioration of the peel strength. The amount of water absorbed was relatively low; thus the peel strength was relatively unaffected.
Source Year: 2014
Keywords: Conventional cure system; EV cure system; Hydrocarbon oil; Peel strength